The Impact of Training and Development and Supervisor Support on Employees Retention in Academic Institutions: The Moderating Role of Work Environment - Palwasha Bibi; Ashfaq Ahmad; Abdul Halim Abdul Majid (Gadjah Mada International Journal of Business, 2018)
This study investigated the impact of training and development and supervisors support on employees retention. Furthermore, the current study also investigates the moderating effect of the work environment on the relationship between training and development, supervisors support, and employees’ retention. A survey was undertaken to collect data from 250 faculty members working in public sector universities in Pakistan. PLS path modeling was employed to analyze the data. The results revealed that training and development and the support of the supervisors had a significant relationship with the retention of employees. Similarly, the results also revealed that the work environment moderated the relationship between training and development, supervisors support, and employees’ retention. Finally, the implications, limitations and recommendations for further research were discussed.